2012
DOI: 10.1021/jp305045w
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of tRNA Aminoacylation: Single Turnover to Steady-State Kinetics of tRNA Synthetases

Abstract: Aminoacyl-tRNA synthetases (aaRS) catalyze the bimolecular association reaction between amino acid and tRNA by specifically and unerringly choosing the cognate amino acid and tRNA. There are two classes of such synthetases that perform tRNA-aminoacylation reaction. Interestingly, these two classes of aminoacyl-tRNA synthetases differ not only in their structures but they also exhibit remarkably distinct kinetics under pre-steady-state condition. The class I synthetases show initial burst of product formation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In addition, we only addressed four possible criteria, but other characteristic properties may also be optimized to support the functionality of biological systems. It would also be interesting to apply the mathematical formalism and the ranking method to other enzymatic systems that display high fidelity (i.e., low error rates) due to the presence of the KPR mechanism, e.g., aminoacyl-tRNA synthetase. ,, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we only addressed four possible criteria, but other characteristic properties may also be optimized to support the functionality of biological systems. It would also be interesting to apply the mathematical formalism and the ranking method to other enzymatic systems that display high fidelity (i.e., low error rates) due to the presence of the KPR mechanism, e.g., aminoacyl-tRNA synthetase. ,, …”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to apply the mathematical formalism and the ranking method to other enzymatic systems that display high fidelity (i.e., low error rates) due to the presence of the KPR mechanism, e.g., aminoacyl-tRNA synthetase. 22,36,37 ■ ASSOCIATED CONTENT * S Supporting Information…”
Section: ■ Conclusionmentioning
confidence: 99%
“…We presented an augmented kinetic scheme that included the role of water and employed the versatile technique of first passage time distribution to obtain time-dependent rate. The theory explained discrepancy between single turn over and steady state rate for both class I and class II enzymes [10].…”
Section: Introductionmentioning
confidence: 93%
“…In a previous study, we investigated the catalytic process of aminoacylation of tRNA. We showed that for class I synthetases, the steady state and single molecular events provide somewhat different kinetics [10]. We presented an augmented kinetic scheme that included the role of water and employed the versatile technique of first passage time distribution to obtain time-dependent rate.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, master equations involved in all such problems are solved by employing the method of mean first passage time [32,36,37], Gillespie algorithm or straight forward numerical integration. We adopt both the deterministic approach by solving differential equations numerically and stochastic simulation by employing Gillespie algorithm [38,39].…”
Section: In the Scheme The Primary Events Are The Following: (1) Thementioning
confidence: 99%